Donor conditioning and organ pre-treatment prior to kidney transplantation: reappraisal of the available clinical evidence - Schnülle, Peter; Krämer, Bernhard (Journal of Clinical Medicine, 2024)
Therapeutic measures aimed at optimising organ function prior to transplantation—whether by conditioning the donor after determination of brain death or by improving organ preservation after kidney removal—have the potential to enhance outcomes after transplantation. The particular advantage is that, unlike any optimised immunosuppressive therapy, a favourable effect can be achieved without side effects for the organ recipient. In recent years, several such measures have been tested in controlled clinical trials on large patient cohorts following kidney transplantation. Hypothermic pulsatile machine perfusion, in particular, has become the focus of interest, but interventions in the donor prior to organ removal, such as the administration of low-dose dopamine until the start of cold perfusion as an example of conditioning antioxidant therapy and therapeutic donor hypothermia in the intensive care unit after brain death confirmation, have also significantly reduced the frequency of dialysis after transplantation with far less effort and cost. With regard to benefits for graft survival, the database for all procedures is less clear and controversial. The aim of this review article is to re-evaluate the available clinical evidence from large multicentre controlled trials, which have also significantly influenced later meta-analyses, and to assess the significance for use in routine clinical practice.
Gesehen am 06.02.2025